Willard family papers - Willard, Antonia Ford, 1838-1871.; Willard, Belle Layton Wyatt, 1873-1954.; Willard, Joseph Clapp, 1820-1897.; Willard, Joseph Edward, 1865-1924.; Wyatt, Joseph W.
Correspondence, letterbooks, notebooks, diaries, subject files, business and financial records, and other papers. Papers of Joseph Edward Willard reflect his activities as a member of the Virginia House of Delegates (1894-1902), member of the staff of Maj. Gen. Fitzhugh Lee in Cuba during the Spanish-American War, lieutenant governor of Virginia (1902-1906), and U.S. ambassador to Spain (1913-1921). Papers (1865-1955) of his wife, Belle Layton Wyatt Willard deal primarily with family matters, genealogies of the Anderson, Herbert, Randolph, and Wyatt families, and financial affairs and include letters (1922) from her daughter, Elizabeth Willard Herbert, relating to the discovery of the tomb of Tutankhamen by George Edward Stanhope Molyneux Herbert, earl of Carnarvon. Papers of his mother, Antonia Ford Willard, relate to her alleged espionage work for the Confederacy aiding Generals John S. Mosby and Jeb Stuart and her arrest by and subsequent marriage to Major Joseph Clapp Willard, whose papers document his Civil War experiences and business interests in Washington, D.C.
Papers of Joseph W. Wyatt include extensive records of the Willard Hotel, Washington, D.C., and the Virginia Hotel Company, a real estate holding company. Other records relate to the Fairfax Development Corporation, Rappahannock Land Development Corporation, and Richmond and Rappahannock River Railway Company. Correspondents include Hilaire Belloc, Henry F. Hollis, Edward M. House, Theodore Roosevelt, Elihu Root, Jr., Augusta Saint-Gaudens, Homer Saint-Gaudens, and Woodrow Wilson.
Microfilm edition of bill book 3, 1860-1861, available
Microfilm produced from originals in the Manuscript Division.
Library of Congress Geography and Map Division.
Library of Congress Prints and Photographs Division.
Family active in the social and political life of Virginia and Washington, D.C.
Collection material in English.
Keywords: Belloc, Hilaire, -- 1870-1953 -- Correspondence; Carnarvon, George Edward Stanhope Molyneux Herbert, -- Earl of, -- 1866-1923.; Herbert, Elizabeth Willard -- Correspondence; Hollis, Henry French, -- 1869-1949 -- Correspondence; House, Edward Mandell, -- 1858-1938 -- Correspondence; Lee, Fitzhugh, -- 1835-1905.; Mosby, John Singleton, -- 1833-1916.; Roosevelt, Theodore, -- 1858-1919 -- Correspondence; Root, Elihu, -- 1881-1967 -- Correspondence; Saint-Gaudens, Augusta -- Correspondence; Saint-Gaudens, Homer, -- 1880- -- Correspondence; Stuart, Jeb, -- 1833-1864.; Tutankhamen, -- King of Egypt; Wilson, Woodrow, -- 1856-1924 -- Correspondence; Anderson family; Herbert family; Randolph family; Willard family; Wyatt family; Fairfax Development Corporation; Rappahannock Land Development Corporation; Richmond and Rappahannock River Railway Company; Virginia. -- General Assembly. -- House of Delegates; Virginia Hotel Company; Willard Hotel (Washington, D.C.); Espionage, Confederate; Hotels -- Washington (D.C.); Railroads -- Virginia; Real estate development -- Virginia; Real estate development -- Washington (D.C.); Spanish-American War, 1898 -- Campaigns -- Cuba; Spies -- Confederate States of America; Spain -- Foreign relations -- United States; Diplomatic and consular service, American -- Spain; United States -- Foreign relations -- Spain; United States -- History -- Civil War, 1861-1865.; United States -- History -- Civil War, 1861-1865 -- Women; Virginia -- Politics and government -- 1865-1950.; Virginia -- Social life and customs; Washington (D.C.) -- Social life and customs